Financial management practices and life satisfaction: The mediating role of financial satisfaction - Hidayat, Taufik (Journal of Management and Business Insight, 2024)
Purpose-Every individual desires to fulfill all life satisfaction with their income. With their income, each individual needs to recognize financial management practices to achieve their life satisfaction. According to certain research, life satisfaction is impacted by financial management practices and financial satisfaction.  By using good financial management practices, one can attain both financial and life satisfaction.  This study aims to analyze the role of financial management practices on life satisfaction with financial satisfaction as a mediator. Design/Methodology/Approach-This study used purposive sampling, which was selected based on certain criteria, and obtained 150 respondents. The research data collection used a questionnaire distributed online using Google Forms addressed to Bank Rakyat Indonesia employees in Yogyakarta, Indonesia. The analytical tool used was Smart PLS with a bootstrapping process. Findings-This study explains that financial management practices do not affect life satisfaction. Financial satisfaction has a positive effect on life satisfaction, and financial management practices positively affect life satisfaction through financial satisfaction as a mediating variable. Research limitations/implications-This research has limitations. The number of respondents is minimal, so it needs to be increased. The respondents do not represent all Bank Rakyat Indonesia employees in all regions of Indonesia. Therefore, the results of this study cannot interpret the condition of life satisfaction of Bank Rakyat Indonesia employees in all areas of Indonesia or bank employees in general. Originality/value-This research is still very minimal and was conducted by previous researchers who used the objects of Bank Rakyat Indonesia employees in Yogyakarta, Indonesia. Previous studies generally used different objects or were in certain regions.